Legal Protection for Workers who Have Harmed Employers: Case Study of Supreme Court Verdict Number 702K/Pdt.Sus-Phi/2021 - Sonia Amelia; Ega Permatadani; Ida Ayu Rosida; Rifda Ayu Akmaliya; Anang Dony Irawan (Indonesia Law Reform Journal, 2023)
The purpose of this research is to find out how legal protection for workers has harmed employers so that workers have been laid off. The type of research used in this study is normative research using the nature of the law approach as well as the theoretical point of view from scientific books and journals that function to provide solutions to existing legal problems. The results show that even though Article 164 paragraph (3) of Law Number 13 of 2003 must provide severance pay, award money, and services during the employee's working period and provide compensation. When workers are proven to be unproductive at work or have problems with the detriment of the employer, the employer can take action to terminate the employment relationship with the worker. From there, the Law does not prohibit companies from taking efficiency measures, but these efficiency actions are no longer valid if there are procedures or reasons that are not in accordance with the applicable regulatory requirements. With the existence of Law No. 13 of 2003 concerning Manpower, I hope that it can implement various national instruments that have been ratified, for example labor rights. This ambiguity makes the Indonesian people have to have strong policies and regulations on labor rights regulations, so that they can restore the wheels of Indonesia's slumping economy. Keywords: Labor; Legal Protection; Termination of Employment.   Abstrak Tujuan penelitian yakni untuk mengetahui bagaimana perlindungan hukum bagi para pekerja yang telah merugikan pengusaha sehingga sampai para pekerja di PHK. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian normatif dengan memakai sifat pendekatan Undang-Undang serta sudut pandang teoritis dari buku dan jurnal ilmiah yang berfungsi untuk memberikan solusi terhadap permasalahan hukum yang ada. Hasil penelitian menunjukan bahwa Saat pekerja terbukti tidak produktif dalam bekerja atau memiliki masalah sampai merugikan pengusaha disitu pengusaha bisa mengambil tindakan untuk memutuskan hubungan kerja dengan pekerja. Dari situ Undang-Undang tidak melarang perusahaan untuk melakukan tindakan efisiensi namun tindakan efiensi tersebut menjadi tidak berlaku lagi jika ada prosedur atau alasan yang tidak sesuai dengan syarat peraturan yang berlaku. Adanya Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan saya harap bisa melaksanakan berbagai instrument nasional yang telah diratifikasi contohnya hak hak tenaga kerja. Ketidakjelasan tersebut membuat bangsa Indonesia harus memiliki kebijakan dan peraturan yang kuat atas peraturan hak para tenaga kerja, sehingga bisa mengembalikan roda perekonomian Indonesia yang terpuruk ini. Kata Kunci: Tenaga Kerja; Perlindungan Hukum; Pemutusan Hubungan Kerja.